Sleep Deprivation and Divergent Toll-like Receptor-4 Activation of Cellular Inflammation in Aging - Carroll, Judith E. (Sleep, 2015)
OBJECTIVES: Sleep disturbance and aging are associated with increases in inflammation, as well as increased risk of infectious disease. However, there is limited understanding of the role of sleep loss on age-related differences in immune responses. This study examines the effects of sleep deprivation on toll-like receptor activation of monocytic inflammation in younger compared to older adults. DESIGN, SETTING, AND PARTICIPANTS: Community-dwelling adults (n = 70) who were categorized as younger (25–39 y old, n = 21) and older (60–84 y old, n = 49) participants, underwent a sleep laboratory-based experimental partial sleep deprivation (PSD) protocol including adaptation, an uninterrupted night of sleep, sleep deprivation (sleep restricted to 03:00–07:00), and recovery. MEASUREMENT AND RESULTS: Blood samples were obtained each morning to measure toll-like receptor-4 activation of monocyte intracellular production of the inflammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Partial sleep deprivation induced a significant increase in the production of IL-6 and/or TNF-α that persisted after a night of recovery sleep (F(2,121.2) = 3.8, P < 0.05). Age moderated the effects of sleep loss, such that younger adults had an increase in inflammatory cytokine production that was not present in older adults (F(2,121.2) = 4.0, P < 0.05). CONCLUSION: Older adults exhibit reduced toll-like receptor 4 stimulated cellular inflammation that, unlike in younger adults, is not activated after a night of partial sleep loss. Whereas sleep loss increases cellular inflammation in younger adults and may contribute to inflammatory disorders, blunted toll-like receptor activation in older adults may increase the risk of infectious disease seen with aging. CITATION: Carroll JE, Carrillo C, Olmstead R, Witarama T, Breen EC, Yokomizo M, Seeman TE, Irwin MR. Sleep deprivation and divergent toll-like receptor-4 activation of cellular inflammation in aging. SLEEP 2015;38(2):205–211.